The worth of anonymous feedback - Dreher, Heinz; Maurer, H. (European Commission, 2006)
Prima facie it is accepted that anonymity is an important feature of eLearning systems. It is easy to implement. But this simplicity belies its more serious implications, especially regarding the worth which can be attached to results derived from the interpretation and analysis of anonymously collected data. A sample of eLearning implementation cases is reviewed from the point of view of anonymously collected data for evaluation of educational quality. A reiteration of an earlier analysis of levels of anonymity leads to the introduction of the Anonymity-Purpose-Worth matrix. It is contended that if the matrix is used to characterise the data collection and analysis in eLearning evaluation settings, the worth of feedback can be better appraised and acted upon. Practitioners, researchers, and students in the eLearning field will benefit as the anonymity conditions will be clearly documented in a standardised and comparable manner.